The effect of a splitter plate on the flow around a finite prism. (November 2015) - Ogunremi, A.R.; Sumner, D.
Abstract: The effect of a wake-mounted splitter plate on the flow around a surface-mounted finite-height square prism was investigated experimentally in a low-speed wind tunnel. Measurements of the mean drag force and vortex shedding frequency were made at Re=7.4×10 4 for square prisms of aspect ratios AR=9, 7, 5 and 3. Measurements of the mean wake velocity field were made with a seven-hole pressure probe at Re=3.7×10 4 for square prisms of AR=9 and 5. The relative thickness of the boundary layer on the ground plane was δ / D =1.5–1.6 (where D is the side length of the prism). The splitter plates were mounted vertically from the ground plane on the wake centreline, with a negligible gap between the leading edge of the plate and rear of the prism. The splitter plate heights were always the same as the heights of prisms, while the splitter plate lengths ranged from L / D =1 to 7. Compared to previously published results for an "infinite" square prism, a splitter plate is less effective at drag reduction, but more effective at vortex shedding suppression, when used with a finite-height square prism. Significant reduction in drag was realized only for short prisms (of AR≤5) when long splitter plates (of L / D ≥5) were used. In contrast, a splitter plate of length L / D =3 was sufficient to suppress vortex shedding for all aspect ratios tested. Compared to previous results for finite-height circular cylinders, finite-height square prisms typically need longer splitter plates for vortex shedding suppression. The effect of the splitter plate on the mean wake was to narrow the wake width close to the ground plane, stretch and weaken the streamwise vortex structures, and increase the lateral entrainment of ambient fluid towards the wake centreline. The splitter plate has little effect on the mean downwash. Long splitter plates resulted in the formation of additional streamwise vortex structures in the upper part of the wake. Highlights: Flow around a finite square prism with a splitter plate was studied experimentally. The effects of splitter plate length and prism aspect ratio were considered. Maximum drag reduction was found for short prisms fitted with long splitter plates. A short splitter plate is needed for vortex shedding suppression. The splitter plate narrows the wake and weakens the mean tip vortex structures.